2011
DOI: 10.1021/la2002783
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistance and Durability of Superhydrophobic Surface Formed on Magnesium Alloy Coated with Nanostructured Cerium Oxide Film and Fluoroalkylsilane Molecules in Corrosive NaCl Aqueous Solution

Abstract: The corrosion resistant performance and durability of the superhydrophobic surface on magnesium alloy coated with nanostructured cerium oxide film and fluoroalkylsilane molecules in corrosive NaCl aqueous solution were investigated using electrochemical and contact angle measurements. The durability of the superhydrophobic surface in corrosive 5 wt% NaCl aqueous solution was elucidated. The corrosion resistant performance of the superhydrophobic surface formed on magnesium alloy was estimated by electrochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
120
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(123 citation statements)
references
References 53 publications
3
120
0
Order By: Relevance
“…[1][2][3][4][5] There has been considerable focus on understanding their wettability 6,7 and developing them for a wide range of applications including droplet impact resistance, [8][9][10][11][12][13] anti-icing, [14][15][16][17][18][19] dropwise condensation, [20][21][22][23][24] electro-wetting, 25,26 drag reduction, [27][28][29][30][31][32] evaporation, 33,34 and anti-corrosion. [35][36][37][38] An important challenge for broad applicability of these hydrophobic materials is their limited robustness. 3,4,39 Most approaches for fabricating superhydrophobic surfaces involve texturing a polymeric hydrophobic material or coating a textured hydrophilic material with a polymeric hydrophobic modifier such as organosilanes or thiols.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] There has been considerable focus on understanding their wettability 6,7 and developing them for a wide range of applications including droplet impact resistance, [8][9][10][11][12][13] anti-icing, [14][15][16][17][18][19] dropwise condensation, [20][21][22][23][24] electro-wetting, 25,26 drag reduction, [27][28][29][30][31][32] evaporation, 33,34 and anti-corrosion. [35][36][37][38] An important challenge for broad applicability of these hydrophobic materials is their limited robustness. 3,4,39 Most approaches for fabricating superhydrophobic surfaces involve texturing a polymeric hydrophobic material or coating a textured hydrophilic material with a polymeric hydrophobic modifier such as organosilanes or thiols.…”
mentioning
confidence: 99%
“…Furthermore, their results show that a superhydrophobic coating can lead to at most a 300% reduction in the corrosion current density of an aluminum surface compared to an untreated aluminum surface. Ishizaki et al [100] also showed that the corrosion current density of a superhydrophobic surface was decreased by more than one order of magnitude as compared to that of the uncoated one. These results indicate that the superhydrophobic film has good corrosion resistance.…”
Section: Ii-5-3-corrosion Resistancementioning
confidence: 99%
“…In order to simulate the influence of rainwater on a superhydrophobic coating, the surfaces are immersed in various pH solutions [95,97,[100][101][102][103][104][105]. Momen et al [95] studied the stability of the surfaces spray-coated with silicone rubber/ZnO/SiC>2 composites after immersion in different pHs (4, 6, 7 and 10) in order to simulate rainwater conditions.…”
Section: Ii-5-2-effect Of Different Phmentioning
confidence: 99%
See 1 more Smart Citation
“…Nano-sized cerium oxide incorporated in nickel, aluminium, and magnesium matrices improved the corrosion resistance and wear resistance (Arurault et al 2004;Low et al 2006;Chandrasekar and Pushpavanam 2008;Xue et al 2010). A recent report showed the development of super-hydrophobic surface of magnesium alloys and aluminium alloys using nano-cerium-oxide thin films (Ishizaki et al 2011;Liang et al 2013). The commonly employed method to prevent corrosion in mild steel is to provide a permanent impermeable coating.…”
Section: Introductionmentioning
confidence: 99%